Student behavior toward the implementation of smoke-free area policy in health higher education institutions: A descriptive study - Lina Oktavia; Toto Harto (School of Health Sciences Al-Ma'arif, 2025)
Background Smoke-Free Area (SFA) policies are an essential public health intervention aimed at reducing tobacco exposure and promoting a healthy environment, particularly in higher education institutions. However, compliance remains a challenge, even in health-focused universities where students are expected to model healthy behavior. Objective This study aims to analyze student behavior toward the implementation of the Smoke-Free Area (SFA) policy in a health higher education institution. Methods A descriptive quantitative study was conducted among 32 male students at STIKes Al-Maarif Baturaja using a total sampling technique. A structured questionnaire was used to assess students’ knowledge, attitude, and practice regarding the SFA policy. Data were analyzed using univariate descriptive statistics. Results The findings revealed that while most students demonstrated a positive attitude toward the SFA policy (62.5%), only 28.1% had good knowledge and 18.8% showed favorable practices. The majority exhibited moderate levels of knowledge (37.5%) and practice (50%), with 34.4% showing poor knowledge and 31.2% demonstrating poor adherence in practice. Students were aware of the health risks of smoking and supported policy enforcement, but lacked sufficient knowledge of policy implementation and institutional mechanisms. Conclusion There is a notable gap between students' positive attitudes and their actual practices and knowledge regarding the SFA policy. This misalignment indicates that students are not yet fully engaged as active change agents in promoting a smoke-free campus. It is crucial for institutions to strengthen educational efforts, provide clear policy communication, and engage students in policy enforcement mechanisms. Integrating SFA values into academic and extracurricular activities may foster better awareness and behavioral alignment among health students.